1444PPulmonary tumour-draining vein exosomal lincRNA-p21 levels impacts non-small cell lung cancer prognosis. (1st October 2019) - Castellano, J J; Navarro, A; Molins, L; Canals, J; Marrades, R; Viñolas, N; Moises, J; Casadevall, M; Li, Y; Han, B; Martinez, D; Martin, J; et al.
Abstract: Background: In resected non-small cell lung cancer (NSCLC) considerable recurrence rates has been reported (30%). Tumor secretes small extracellular vesicles known as exosomes, which plays a role in the metastasis process. Pulmonary tumor-draining vein blood has proved to be better source than peripheral vein to analyze the prognosis impact of exosomes (Navarro A, et al. Cancers 2019). LincRNA-p21 is a long non-coding RNA which upregulation in tumor tissue induced by hypoxia was related to poor prognosis in NSCLC (Castellano JJ. et al. JTO 2016). We aimed to evaluate the presence of lincRNA-p21 in exosomes and its potential as prognosis biomarker in resected NSCLC patients. Methods: H23 and H1299 NSCLC cell lines were cultured in exosome-free medium 48h under normoxic/hypoxic conditions. LincRNA-p21 was inhibited using a siRNA and quantified using a TaqMan assay. Exosomes were purified by ultracentrifugation and characterized by electron microscopy, western blot and Nanosight. LincRNA-p21 was analyzed in exosomes from pulmonary tumor-draining vein, obtained during surgery, from 54 NSCLC patients. Results: LincRNA-p21 was present in exosomes showing 18 times more representation than in their origin cells. Under hypoxic conditions exosomal lincRNA-p21 was upregulated in both cell lines (p < 0.05). Cellular lincRNA-p21 silencing resulted in a reduction in exosomal lincRNA-p21 (p = 0.04) indicating a relation between cellular and exosomal levels. The analysis in patient samples showed that lincRNA-p21 was present in patient exosomes obtained from tumor-draining vein. The survival analysis showed that high exosomal lincRNA-p21 levels were associated with shorter time to relapse (TTR) (37 vs 56 months; p = 0.03) and shorter overall survival (OS) (46 vs 66 months; p = 0.04). In the multivariate analysis exosomal lincRNA-p21 emerged as an independent prognostic marker for TTR (HR: 3.1; 95%CI: 1.02-9.4; p = 0.04) and OS (HR: 5.3; 95%CI: 1.6-17.2; p = 0.006) together with disease stage. Conclusions: Tumor exosomes carry LincRNA-p21, which increases under hypoxia, and its analysis in tumor-draining vein arises as a promising prognosis marker. Legal entity responsible for the study: The authors. Funding: SAF2017-88606-P (AEI/FEDER, UE). Disclosure: All authors have declared no conflicts of interest.